2012
DOI: 10.2188/jea.je20110101
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Fabry Disease Among Beneficiaries of the Specified Disease Treatment Research Program in Japan

Abstract: BackgroundFabry disease (FD) is a rare X-linked lysosomal storage disorder and is included in the Specified Disease Treatment Research Program in Japan, which subsidizes medical care for beneficiaries with rare and other, designated diseases. However, no report on the epidemiologic features of Fabry disease has been published in Japan.MethodsWe used clinical research data reports submitted to the program between 2003 and 2008 to assess the epidemiologic features of 315 beneficiaries with FD.ResultsOf the 315 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In Japan, various small studies have suggested a prevalence of 0.16-1.2% among ESRD patients treated with chronic hemodialysis (2,15,16). Notably, Tsuboi et al (17) reported the prevalence of Fabry disease in Japan to be 0.25 cases per 100,000 individuals. Therefore, the true prevalence of this disease may be much higher in chronic hemodialysis patients than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, various small studies have suggested a prevalence of 0.16-1.2% among ESRD patients treated with chronic hemodialysis (2,15,16). Notably, Tsuboi et al (17) reported the prevalence of Fabry disease in Japan to be 0.25 cases per 100,000 individuals. Therefore, the true prevalence of this disease may be much higher in chronic hemodialysis patients than in the general population.…”
Section: Discussionmentioning
confidence: 99%